The formation of Laurentia: evidence from shear wave splitting - Liddell,M; Bastow,ID; Darbyshire,FA; Gilligan,A; Pugh,S (Earth and Planetary Science Letters, 2017)
The northern Hudson Bay region in Canada comprises several Archean cratonic nuclei, assembled by a number of Paleoproterozoic orogenies including the Trans-Hudson Orogen (THO) and the Rinkian–Nagssugtoqidian Orogen. Recent debate has focused on the extent to which these orogens have modern analogues such as the Himalayan–Karakoram–Tibet Orogen. Further, the structure of the lithospheric mantle beneath the Hudson Strait and southern Baffin Island is potentially indicative of Paleoproterozoic underthrusting of the Superior plate beneath the Churchill collage. Also in question is whether the Laurentian cratonic root is stratified, with a fast, depleted, Archean core underlain by a slower, younger, thermally-accreted layer. Plate-scale process that create structures such as these are expected to manifest as measurable fossil seismic anisotropic fabrics. We investigate these problems via shear wave splitting, and present the most comprehensive study to date of mantle seismic anisotropy in northern Laurentia. Strong evidence is presented for multiple layers of anisotropy beneath Archean zones, consistent with the episodic development model of stratified cratonic keels. We also show that southern Baffin Island is underlain by dipping anisotropic fabric, where underthrusting of the Superior plate beneath the Churchill has previously been interpreted. This provides direct evidence of subduction-related deformation at 1.8 Ga, implying that the THO developed with modern plate-tectonic style interactions.